Analysis of Crude Palm Oil Quality Using Statistical Quality Control in the Palm Oil Industry - Viarani M, Suci Oktri; Lubis, Rizki Fadhillah; Jumita, Ses; Siregar, Rahmad Syukur (JASc (Journal of Agribusiness Sciences), 2022)
This study aims to study the Quality Control Analysis of Crude Palm Oil Quality in the Palm Oil Processing Industry in Kampar Regency, Riau Province. Looking for factors causing quality deviations of Crude Palm Oil and finding solutions to problems causing these quality deviations. The test results using the tools on Statistical Quality Control show that the Free Fatty Acids experience quality deviations. The factors that cause it are humans, methods, machines and raw materials. In addition to the causes of the problem, this study also tries to provide solutions to problems that arise.